Transmission and pathology of Streptococcus inane in monosex Nile tilapia (Oreochromis niloticus) in aquaculture of Bangladesh - Md. Mer Mosharraf Hossain; Amimul Ehsan; Md. Anisur Rahman; Monjurul Haq; Md. Bazlur Rashid Chowdhury (Journal of Fisheries, 2014)
Streptococcus iniae is a major fish pathogen, recently emergent outbreaks were recorded in commercially cultured monosex Nile tilapia (Oreochromis niloticus) result in significant losses termed “streptococcosis”-causes unusual appearances with multi-focal pin-point haemorrhages, abscesses, necrosis and ascites in skin, fin, muscle, liver, spleen, kidney, blood, interstitial fluid specially in central nervous system and brain. This disease was more prevalent (>26%) at summer when the water temperature was approximately >25oC, percentage of mortality was higher >41% during the overcrowding and improper water chemistry. Raised levels of glucose and ammonium in blood serum causes reduced number of free blood cells released into the haemolymph to stomach and gut, result in refrain from eating in diseased tilapia. Stocking density (200 fish/decimal; class IV) had significant effect (P<0.01) on the total production (5,000 to 5,500 kg/ha). S. iniae in the circulating blood cells, extra-tubular haemal spaces containing blood vessels, fixed phagocytes in the hepatopancreas (gastrointestinal tract), bacteria-like particles in the brain tissue, vacuum and necrosis in hepatocytes revealed with histopathology. In vitro study revealed that cohabitation of dead or infected fish with healthy fish resulted infection (horizontal transmission mechanism) to the healthy fish.